Human Brain Microwave Imaging Signal Processing: Frequency Domain (S-parameters) to Time Domain Conversion - Chew, Kim Mey; Rubita, Sudirman; Norhudah, Seman; Yong, Ching Yee (Scientific Research, 2013)
The paper presents the microwave signal processing method using MATLAB based on the result of microwave imaging system simulation developed using Computer Simulation Technology (CST). The simulation system contains a transmitting/receiving antenna, human brain and a tumor inside the brain model. The source signal, microwave signal operates from 1 to 10 GHz. The generated scattering parameters (S-parameters) are in frequency domain form. This paper describes in detail regarding the signal conversion from frequency domain to time domain through proposed Inverse Fast Fourier Transform (IFFT) method as well as the noise filtering process. Peaks detection process was performed in order to identify the time delay of the reflection points at different Y-axis positions.